Tectonics and Geological Factors Controlling Cleat Development in the Barito Basin, Indonesia - Sapiie, Benyamin; Rifiyanto, Arif (Journal of Engineering and Technological Sciences, 2017)
Cleats are natural fractures within coal seams. This paper presents the results of regional cleat mapping and characterization in relation to coalbed methane (CBM) exploration and development in the Barito Basin, South Kalimantan, Indonesia involving two major coal layers, namely the Late Eocene Tanjung Formation and Early to Middle Miocene Warukin Formation with thicknesses ranging from 2 to 50 m. The coal is classified as lignite to subbituminous with calorific values ranging from 6000-8000 Cal/gr with ash content 0.68-17.42%. We applied two methods of cleat measurement, i.e. scanline and window sampling using a 100 x 100 cm grid. More than 20,000 cleats were measured from 65 scanline and 37 window sampling locations. The results revealed that face and butt cleats are predominantly oriented in the WNW-ESE and NNE-SSW directions, respectively. The results showed that cleat density increases related to structural position such as fold hinge and fault zone. The formation of the cleats may be influenced by several geological processes, where the cleats, which form during coalification, are superimposed by later processes such as fluid pressure and tectonic stresses and are seemingly also affected by the composition of the coal.